Sistematización de la experiencia de valoración de cargos por puntos de la empresa Licoram - Cuarán Aráuz, Mishel Verónica (2018)
This systematization is directed to the need of the LICORAM company to implement a salary system based on points, which allows it to have a scientific backing of the human talent it possesses. Likewise, having a support study to make decisions within the company results in the analysis of a set of measures that directly encompass employee job satisfaction; work that serves, as a systematization of their aptitudes and skills and at the same time characterizes each position and therefore their corresponding remuneration. The company LICORAM presents some problems derived from the absence of this system of salaries by points, which through this systematization show signs of appeasement. Improving this system allows the company to position its main objectives. Thus, this systematization presents an alternative methodology that will allow to save certain characteristics that diminish the participation of employees within the company and raises a relationship between salary and position; fair relationship, associated with the changing qualities of workers and their functions.